Coverage assessment survey following trachoma mass drug administration (MDA) in six districts of Oromia, Western Ethiopia, 2017. - Tariku Tesfaye Bekuma; Getu Mosisa Kebebew; Zelalem Desalegn Waktole; Jote Markos Cafo; Desalegn Wirtu; Solomon Gaddisa (PLoS Neglected Tropical Diseases)
Background Trachoma is a contagious infection of the eye by specific strains of the bacteria Chlamydia trachomatis. It is the leading cause of blindness worldwide. Mass drug administration (MDA) with azithromycin is a cornerstone of World Health Organization (WHO)'s global effort to eliminate trachoma by 2020. This coverage survey was aimed to assess trachoma post-mass drug administration (MDA) coverage among six selected districts of East Wollega, Horo Guduru Wollega, and West Shewa zones in2017. Methods A community based cross-sectional coverage survey was conducted. The sample size was calculated automatically using Coverage Survey Builder (CSB) tool in microsoft excel. Thirty segments were selected per each selected districts of the three zones. A separate Results Entry Form for each district surveyed was completed, saved and uploaded directly into the online Coverage Survey Analysis Tool to estimate the surveycoverage and the program reach along with the corresponding 95% confidence limits and design effects. EPI-INFO 7.0 and SPSS version 20 was used for further analysis of survey data. Result A total of 1,747 households were surveyed, out of which 10,700 individuals were interviewed. Most respondents (95.1%) stated that they heard about trachoma MDA and most of them replied that they got the information from health workers. Program reach ranged between 89.5% in Jimma Geneti district and 94.8% in Dirre Hinchini district. The most common mentioned reasons for not having taken azithromycin included not knowing about the campaign, fear of side effects and being absent during the MDA campaign. Conclusion In this survey, four of the six districts met the target threshold (i.e. 80%) for effective coverage; Ambo rural and Jimma Geneti did not meet the target threshold.Therefore, programmatic improvements should be made for the future campaign to reach the expected thresholds while the campaign in four of the six districts should be encouraged.